2021
DOI: 10.1038/s41598-021-93949-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of community, famliy and early individual factors with body mass index z-scores trajectories among Chinese children and adolescents

Abstract: The prevalence of childhood overweight and obesity is increasing. This study aimed to examine trajectories of BMI z-scores among Chinese children and the potential determinants including early individual, family and community factors. Group-based trajectory modeling was employed to identify BMI z-scores trajectories of children aged 2–18 years using the five waves data (2010, 2012, 2014, 2016, and 2018) of the China Family Panel Studies (CFPS). Multivariate logistic regression was conducted to determine the as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…Mosli et al 39 showed that children who did not experience the birth of any siblings by the time they were in the first grade had 2.94 greater odds of obesity in the first grade compared with children who experienced the birth of any siblings when they were aged between 36 and 54 months, using data of combined sexes. Liang 40 reported that boys, but not girls, as the only child were more likely to belong in the “rapid rising up to school age and then become‐overweight” trajectory (OR, 2.04; 95% CI 1.45–2.86), which is similar to the present study. These data suggest that public health interventions to prevent childhood overweight need to focus on children from these familial backgrounds 36 …”
Section: Discussionsupporting
confidence: 89%
“…Mosli et al 39 showed that children who did not experience the birth of any siblings by the time they were in the first grade had 2.94 greater odds of obesity in the first grade compared with children who experienced the birth of any siblings when they were aged between 36 and 54 months, using data of combined sexes. Liang 40 reported that boys, but not girls, as the only child were more likely to belong in the “rapid rising up to school age and then become‐overweight” trajectory (OR, 2.04; 95% CI 1.45–2.86), which is similar to the present study. These data suggest that public health interventions to prevent childhood overweight need to focus on children from these familial backgrounds 36 …”
Section: Discussionsupporting
confidence: 89%
“…To make the regression more convincible, this paper introduces a series of family and individual level control variables in the regression. Including: family income(Income), gender(Gender, male = 1, female = 0), educational background (Education,1 for college and above, 0 for the rest), age, party membership (Party, one for yes, 0 for no), number of family members (Family), and the place of household registration (Urban, one for urban areas, 0 for rural areas), marital status (Marriage, one for cohabiting and married, 0 for others) (Liang et al, 2021).…”
Section: Control Variablesmentioning
confidence: 99%
“…The early childhood growth trajectories were proved to be predictive of obesity risk in later life ( 13 ), cardiometabolic risk ( 14 , 15 ), and adult diabetes ( 16 ). A recent birth cohort study evaluated childhood BMI z-score trajectories from age of 2 to 18 and showed that preschool age is a critical window that could predict growth patterns during puberty ( 17 ). Therefore, it is necessary to closely monitor the early childhood growth trajectories, focusing on those at higher risk of later overweight or obesity status, and helping to target specific groups for early intervention.…”
Section: Introductionmentioning
confidence: 99%